2000
DOI: 10.1073/pnas.97.4.1707
|View full text |Cite
|
Sign up to set email alerts
|

The dual functions of Fas ligand in the regulation of peripheral CD8+and CD4+T cells

Abstract: costimulation ͉ homeostasis ͉ peripheral T cell

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 46 publications
6
88
0
Order By: Relevance
“…2B). This difference may be due to the fact that Fas and FasL can also act as costimulators for CD4 + T cells [21]. Nevertheless, when Treg cells were added in addition to the young anti-HA lpr/lpr gld/gld T cells, antibody production was dramatically curtailed and anti-chromatin B cells were not detected in the spleen by immunohistochemistry (Fig.…”
Section: Treg Cells Can Suppress Lpr/lpr Gld/gld T Cell Help For B Cellsmentioning
confidence: 94%
“…2B). This difference may be due to the fact that Fas and FasL can also act as costimulators for CD4 + T cells [21]. Nevertheless, when Treg cells were added in addition to the young anti-HA lpr/lpr gld/gld T cells, antibody production was dramatically curtailed and anti-chromatin B cells were not detected in the spleen by immunohistochemistry (Fig.…”
Section: Treg Cells Can Suppress Lpr/lpr Gld/gld T Cell Help For B Cellsmentioning
confidence: 94%
“…44 Although at this stage we cannot dissect whether a single hepatocyte expresses both of the molecules simultaneously, the display of functional CD95L depends, as in lymphoid cells, on cell activation. 14,44 Because CD95L protein in lymphoid cells is sequestered intracellularly and directed into secretory vesicles, 45 this may prevent or postpone the ligand exposure on the effector surface and initiation of cell death via CD95L-CD95 interaction. The same could be true for hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, reverse signaling via CD27L/CD70 has been shown to induce a subset of leukemic B cells to proliferate vigorously, an effect that is synergistically enhanced by ligation of CD40, but inhibited by the presence of IL-4 (13). Recently, Suzuki and Fink (14,15) further demonstrated that maximal proliferation of CTL requires reverse signaling through FasL. It is also interesting to note that addition of CD137.Fc fusion protein induces a substantial degree of proliferation in human peripheral monocytes (16).…”
Section: Enhanced Secretion Of Ifn-␥ By Activated Th1 Cells Occursmentioning
confidence: 99%
“…Recently, our understanding of the signaling pathways downstream of members of TNFR superfamily has advanced dramatically. In addition, there is growing evidence that ligands of the TNF superfamily, such as CD40 ligand (CD40L/CD154) (9 -11), CD30L (12), CD27 ligand (CD27L/CD70) (13), FasL (14,15), CD137L (16), and OX40L (17), also transduce signals after engagement with their receptors. It has been shown that reverse signaling via CD40L is involved in a range of different immune processes, such as cytokine production, costimulation of T cell activation, and proper formation of germinal centers (10).…”
Section: Enhanced Secretion Of Ifn-␥ By Activated Th1 Cells Occursmentioning
confidence: 99%